Statistical thinking as a tool for critical citizenship in training - Martínez–Castro, Cindy Alejandra (Universidad Nacional del Litoral, 2021)
This paper reports a study that investigated the contributions of statistical thinking to critical citizenship in statistics teacher education. The research participants were ten prospective teachers who were taking a seminar on teaching statistics in a Mathematics Education Bachelor program at a public university in the city of Medellin, Colombia. Participants were invited to develop four statistical investigations in the classroom related to social crises. The primary sources of information were the discussions during the seminar meetings. The analysis was carried out through an initial coding to reduce the volume of information, organize it and find regularities and patterns. The main findings reflect that, through statistical investigations in the classroom, participants followed a cycle of empirical inquiry in which they linked concepts, tools, procedures, reasoning and inference, real dispositions and contexts when approaching to answer the statistical questions raised. This is a contribution to critical citizenship.